The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3892/etm.2018.6769
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell transplantation for the treatment of patients with type�1 diabetes mellitus: A meta‑analysis

Abstract: The efficacy of stem cell (SC) transplantation in patients with type 1 diabetes mellitus (T1DM) has remained to be fully elucidated. In the present study, a systematic review and meta-analysis was performed to determine the clinical outcomes. Electronic databases, including PubMed, MEDLINE, WanFang and the Cochrane Library were screened for relevant studies published until January 13, 2018. The references of retrieved papers, systematic reviews and trial registries were manually screened for additional papers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 56 publications
0
16
1
Order By: Relevance
“…As indicated by the pooled effect in our meta-analysis, MSCs + HSCs and HSCs groups showed significant effects to reduce daily insulin requirement and HbA1c levels, as well as to improve C-peptide levels at 1 year follow-up compared to the baseline. Whereas the MSCs group only showed significant effect to decrease HbA1c levels but no significant effect to reduce daily insulin requirement or to improve C-peptide levels, which was different from the meta-analysis conducted by Gan J et al [45]. As we know that, β cells function will decrease rapidly within years during the natural course of T1DM.…”
Section: Discussioncontrasting
confidence: 70%
“…As indicated by the pooled effect in our meta-analysis, MSCs + HSCs and HSCs groups showed significant effects to reduce daily insulin requirement and HbA1c levels, as well as to improve C-peptide levels at 1 year follow-up compared to the baseline. Whereas the MSCs group only showed significant effect to decrease HbA1c levels but no significant effect to reduce daily insulin requirement or to improve C-peptide levels, which was different from the meta-analysis conducted by Gan J et al [45]. As we know that, β cells function will decrease rapidly within years during the natural course of T1DM.…”
Section: Discussioncontrasting
confidence: 70%
“…The rationale for its use is to arrest β cells autoimmune destruction and generate functional cells. Mesenchymal stromal/stem cells seem attractive as they have been tested for other autoimmune diseases with promising results (16)(17)(18)(19)(20)(21)(22)(23)(24) and do not require immunosuppression, even when allogenic sources are used. In vivo and in vitro studies showed that MSCs are capable of suppressing immune response by inhibiting the maturation of dendritic cells, suppressing T cells function and inducing expansion of regulatory T cells (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…In vivo and in vitro studies showed that MSCs are capable of suppressing immune response by inhibiting the maturation of dendritic cells, suppressing T cells function and inducing expansion of regulatory T cells (16)(17)(18)(19). A recent meta-analysis of the clinical efficacy and safety of stem cell therapy for T1D indicated that the treatment seems relatively safe and effective, but most studies are small, use hematopoietic stem cells with immunosuppression and autologous origin (20). In that meta-analysis, patients with recent-onset T1D that received MSCs (from bone marrow or umbilical cord tissue) did not have significant reduction in HbA1c or improvement in C-peptide levels, but 20% of treated T1D patients achieved exogenous insulin independence at some point (20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the etiology of this disease is still under study, most scientists agree that T2DM is related to the resistance of insulin in muscle cells; briefly, insulin cannot trigger the glucose uptake process into cells 7,16 . For the past decade of stem cell therapy, most studies have used stem cell therapy in type 1 diabetes mellitus to regenerate beta cells in the pancreas [17][18][19] . In recent years, some studies have evaluated the use of stem cells to treat T2DM 14 .…”
Section: Discussionmentioning
confidence: 99%